Collaboration of integrative processes intermediaries supporting supply chain management - Mohd Tamrin, Mohd Izzuddin; Sembok, Tengku Mohd (WSEAS Press, 2012)
The supply chain activities require intensive interactions between the members in the supply chain group. The ongoing interactions are also important after the execution of the pre-planned activities to monitor and restructure the processes in case of deviation occurred in the middle of execution. The authors introduce collaboration algorithms running in an Integrative Information Management Architecture (IIMA). The algorithms are an intermediary processes to provide semi automated assistance to the management team for tighter supply chain integration. The algorithms are designed to undergo six main phases to facilitate continuous monitoring of supply chain activities across the group and supporting process restructuring when inflicted by common supply chain problems. The authors had evaluated the performance of the IIMA with three other systems in simulated environments. The results showed that the IIMA was more stable in its performance compared to other systems in supporting customization processes inflicted with common supply chain problems at both early and later stages of the processes.